An assessment of black axe confraternity cult in Nigeria: Its impact on the university educational system - Surajo, Aminu Zubairu; Karim, A.H.M Zehadul (Serials Publications, 2017)
The thesis focuses attention on the activities of Black Axe Confraternity cult in major Nigerian university campuses. The cult group brings about lack of peace and stability in the campus as a result of incessant violence with the rival cult groups. The activities of Black Axe Confraternity cult started at the University of Benin and spread to various universities. The Black Axe cult members also involves in armed robbery, drug trafficking, kidnapping, election rigging and other political malpractice. Every year newly recruited members were initiated into the cult group and they swear with the oath of secrecy. From that day, they give their allegiance to their leaders. The impacts of Black Axe Confraternity cult includes interruption of the academic calendar, lack of peace of minds, insecurity and uncertainty among students, death and injury of many members including the innocent students, destruction of the university properties, involvement of election violence and civil disobedience. The solutions to the problems of Black Axe Confraternity cult group in Nigerian university campuses comprises of public enlightenment campaign on the negative effect of cultism, moral reorientation, discouraging politicians from assisting the cult member financially, admission based on merit and expulsion of students involved in campus cult violence. The parents, society, government and the religious organizations have greater role to play in bringing an end to the problem which affects the university educational system in Nigerian